The racial trauma handbook for teens : CBT skills to heal from the personal & intergenerational trauma of racism - Hill, Támara (Therapist) (Instant help solutions series., 2023)
"Racial trauma can reverberate for generations, and lead to anxiety, irritability, anger, rage, depression, low self-esteem, shame, and guilt. Teens are especially vulnerable to racial trauma, as they are still developing a sense of self and identity. The Racial Trauma Handbook for Teens provides readers with evidence-based cognitive behavioral therapy (CBT) skills to heal the wounds of personal and intergenerational trauma, increase self-awareness, and build confidence"--